Morphometric Traits as Efficient Indicators of Larval Stage-Specific Plasticity in Silver Pompano, Trachinotus blochii (Lacépède, 1801) - SILPA R.; IBURAHIM S., ABUTHAGIR; SURYA S.; RAMTEKE, KARANKUMAR; DEVADAS, DAYAL; VINEETH P.; LANDGE, ASHA TATERAO (Journal of the Indian Society of Coastal Agricultural Research, 2026)
Morphological development, allometric growth, and behaviour of hatchery-reared silver pompano, Trachinotus blochii were studied from hatching to metamorphosis (0-23 days post-hatch (dph). In view of larval identification, to surpass critical periods in culture practices a total of 230 larval specimens of hatchery reared silver pompano were collected. A total of five post-embryonic stages were identified based on differences in morphology namely; Yolk sac (0-3 dph), Pre flexion (4-10 dph), Flexion (11 dph), Post flexion (12 dph), Juvenile (13-23 dph). The length has progressively increased in each larval stage, ultimately reaching 24 mm by the end of metamorphosis. This study showed that the development of the eye, head, and body depth had slower growth than the fish growth in length. All the morphometric traits efficiently differentiated each larval stage due to differences in stage-specific plasticity. This morphometric, morphological, and allometric study in the larval stage of silver pompano will be a baseline data to strengthen the easy identification of larval stages, improve culture practices and supplement future studies on the species.